2008
DOI: 10.1111/j.1460-9568.2008.06506.x
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic control of the excitability of hindlimb motoneurons in chronic spinal‐transected salamanders

Abstract: The excitability of spinal motoneurons (MNs) is regulated by acetylcholine via the activation of muscarinic receptors. The objective of the present study was to determine whether this cholinergic modulation of MN excitability is altered following a chronic spinal cord transection. Juvenile salamanders (Pleurodeles waltlii) were spinally transected at the mid-trunk level, and patch-clamp recordings from hindlimb MNs in spinal cord slices were performed 9-30 days after transection, with and without bath applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…A similar effect has been reported in a variety of preparations, ranging from mammal atrial myocytes (Sakmann et al, 1983), to thalamic reticular neurons (Mccormick and Prince, 1986), spinal motoneurons (Chevallier et al, 2008), interneurons of striatum (Calabresi et al, 1998), neocortex (Xiang et al, 1998), and hippocampus (McQuiston and Madison, 1999). …”
Section: Discussionsupporting
confidence: 65%
“…A similar effect has been reported in a variety of preparations, ranging from mammal atrial myocytes (Sakmann et al, 1983), to thalamic reticular neurons (Mccormick and Prince, 1986), spinal motoneurons (Chevallier et al, 2008), interneurons of striatum (Calabresi et al, 1998), neocortex (Xiang et al, 1998), and hippocampus (McQuiston and Madison, 1999). …”
Section: Discussionsupporting
confidence: 65%
“…These differences between hypoglossal and lumbar locomotor motoneurons could result from distinct NAergic receptor sub-type expression and/or intracellular coupling (Rekling et al, 2000). The K IR channels contribute to the resting membrane potential and neuronal excitability and for these reasons, they constitute the main targets of numerous G-protein coupled receptors (see for examples Bertrand et al, 2003a,b; Derjean et al, 2003; Chevallier et al, 2008). In the neonatal rat spinal cord, it has been shown that serotonin as NA increases the motoneuron excitability partly via the inhibition of K IR -like current (Kjaerulff and Kiehn, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the above studies we extended the model by the addition of a hyperpolarization activated h-current (I h ) and a persistent sodium current (I NaP ) since it has been demonstrated that blocking these channels can, respectively, slow down or abolish oscillatory behavior (Ryczko et al 2010a). I h was further demonstrated to be present in salamander motoneurons (Chevallier et al 2006(Chevallier et al , 2008b. The default diameter of our tentative salamander locomotor CPG interneurons was chosen as 30 µm (Jovanovic and Burke 2004).…”
Section: The Cell Modelmentioning
confidence: 99%